-6(2x+1)=3x+7-9

Simple and best practice solution for -6(2x+1)=3x+7-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2x+1)=3x+7-9 equation:



-6(2x+1)=3x+7-9
We move all terms to the left:
-6(2x+1)-(3x+7-9)=0
We add all the numbers together, and all the variables
-6(2x+1)-(3x-2)=0
We multiply parentheses
-12x-(3x-2)-6=0
We get rid of parentheses
-12x-3x+2-6=0
We add all the numbers together, and all the variables
-15x-4=0
We move all terms containing x to the left, all other terms to the right
-15x=4
x=4/-15
x=-4/15

You can always share this solution

See similar equations:

| 15=h/2-11 | | -5(z+1)-3(-1-z)=-30 | | -6(2x+1)=3x+79x | | 4.9x+4.5=19.2 | | 2x+26+6=x+23 | | 9=g/2+6 | | y-22=-42 | | -x+5/2=9 | | X+8(1-x)=1 | | 4m+9=5m-8/5 | | -36=-9(6+2x) | | 8=f/2+6 | | 54+x=-78 | | 1+2r+6=3 | | y-17=-46 | | 2r/5=3r | | 6x+10/3=5 | | 5x/3+3=8 | | 5x?1=24 | | 5/6+6(x)=7(x)-2/3 | | 6n+5-10n=4n+4-7n | | 9=6x+2+7x | | 8-7y=10 | | ?14=?(?2x+2) | | 4x+(x+5)=25 | | -2(x+4)-7=-15 | | x/6/x/7=7/6 | | X÷4=90-x | | 8=n/3+7 | | 3/2d+18=1d-3 | | 12+6n=4n+6n | | X^2-25=-4x-4 |

Equations solver categories